Influências dos professores de Educação Física na educação básica para a escolha do curso de licenciatura em Educação Física - Zaneratto, Gabriel Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Este trabalho busca entender como o professor de Educação física influência seus alunos a optarem pela carreira docente e quais fatores de sua conduta e aula exercem algum tipo de inspiração para esse interesse. Diante disso, o objetivo deste estudo foi identificar e analisar os fatores que estabelecem motivação para que ingressantes no ensino superior escolham o curso de licenciatura em Educação Física. A pesquisa foi feita através de uma entrevista semiestruturada com participantes selecionados através de um Google Forms, as entrevistadas foram realizadas via Google meet, com 4 alunas do curso de licenciatura em Educação Física da Unesp - Bauru de 19 a 22 anos que ingressaram entre 2019 a 2022. Os resultados deste trabalho são expressos pelas categorias de análise. 1. Um “bom professor” de Educação Física que nos mostra qual a importância de os alunos entenderem que seus professores são bons independentemente de qual modelo de aula utiliza; 2. Boa relação professor-aluno trazendo como é significativo e fundamental ter uma relação de respeito e troca com os discentes para valorizar e subsidiar o gosto pela profissão; 3. Ensinar conteúdos/conhecimentos que dialoguem com as características e gostos dos alunos, evidencia que trabalhar com assuntos que tenham relação com o gosto e interesse dos alunos também exerce uma função para que os alunos se aproximem da Educação Física. Com base nestes resultados, podemos apontar que há alguns fatores sobre os professores de Educação Física na educação básica que podem sim influenciar os alunos a ingressarem no curso de licenciatura em Educação Física, tal qual, valorizar a carreira docente como um todo. This study seeks to understand how physical education teachers influence their students to choose a teaching career, and which factors in their conduct and classes inspire this interest. Therefore, the objective of this study was to identify and analyze the factors that establish motivation for students entering college to choose a degree course in Physical Education. The research was done through a semi-structured interview with participants selected through a Google Forms, the interviewees were conducted via Google meet, with 4 female students of the undergraduate course in Physical Education at Unesp - Bauru from 19 to 22 years old who entered between 2019 to 2022. The results of this work are expressed by the categories of analysis. 1. having a "good teacher" of Physical Education that shows us the importance of students understanding that their teachers are good regardless of which class model they use; 2. good teacher-student relationship bring how significant and fundamental it is to have a relationship of respect and exchange with students to value and subsidize the taste for the profession; 3. teaching contents/knowledge that dialogue with the characteristics and tastes of students, shows that working with subjects that are related to the taste and interest of students also plays a role for students to approach Physical Education. Based on these results, we can point out that there are some factors about Physical Education teachers in basic education that may influence students to enter a Physical Education undergraduate course, such as valuing the teaching career as a whole.

This study seeks to understand how physical education teachers influence their students to choose a teaching career, and which factors in their conduct and classes inspire this interest. Therefore, the objective of this study was to identify and analyze the factors that establish motivation for students entering college to choose a degree course in Physical Education. The research was done through a semi-structured interview with participants selected through a Google Forms, the interviewees were conducted via Google meet, with 4 female students of the undergraduate course in Physical Education at Unesp - Bauru from 19 to 22 years old who entered between 2019 to 2022. The results of this work are expressed by the categories of analysis. 1. having a "good teacher" of Physical Education that shows us the importance of students understanding that their teachers are good regardless of which class model they use; 2. good teacher-student relationship bring how significant and fundamental it is to have a relationship of respect and exchange with students to value and subsidize the taste for the profession; 3. teaching contents/knowledge that dialogue with the characteristics and tastes of students, shows that working with subjects that are related to the taste and interest of students also plays a role for students to approach Physical Education. Based on these results, we can point out that there are some factors about Physical Education teachers in basic education that may influence students to enter a Physical Education undergraduate course, such as valuing the teaching career as a whole.
Influences of Physical Education teachers in basics education for the choice of the degree course in Physical Education
Keywords: Educação Física; Carreira docente; Escolha profissional; Teaching career; Physical Education; Professional choices